The political economy of educational provision in "white" commercial farming areas: findings from a case study conducted in the Ugie district in the north eastern Cape - Stretton, Natasha Anne (Rhodes University, Faculty of Humanities, Department of Political Studies, 1993)
The under-provision of education for black South Africans has reached crisis proportions. While the education for black people in general is discriminatory and unequal, black rural people suffer further deprivations as there is a serious imbalance in the allocation of resources and the provision of education between urban and rural areas. Black education in the rural areas has been historically neglected for political and socio-economic reasons and, as a consequence, rural blacks have limited or no access to education. The purpose of this' study is to examine an aspect of rural education; viz: black farm schools in the 'white' commercial farming areas. It is argued that the provision of farm schools is intricately linked to the labour requirements of farmers and consequently farm schools cannot be understood independently from the social relations within commercial farming areas. The impact of local decision-making on the process of farm schooling is also significant and is an important aspect of this study. This thesis explores the political and socio-economic processes that have structured the provision of education within a small farming community, looking specifically at the effects of particular interest groups on the provision of black farm schools. The study operates on three levels. The first level provides a theoretical framework within which rural education can be better understood. It is argued that the bias towards urban areas is reflected in the current theoretical debates on the role and function of education Â·in South Africa. As these theories are generally incapable of explaining rural education, an alternative model is proposed. As education cannot be understood in isolation from the rest of society, the second level of the study locates farm schooling within the broader political and socio-economic systems. This is done from two perspectives. The first perspective focuses on black education in general, tracing aspects of its development and highlighting the impact .of economic interests, white political control and black resistances to this development. The neglect of rural education is also contextualised historically and politically. The second perspective looks at rural education at a macro-level. The historical origins of the farm schools system and the effects of the relationship between agricultural capital and the state, and between farmers and farm workers on the process of farm schooling is examined. The final level of the study focuses on the micro-situation and provides an in-depth analysis of the political and socio-economic dynamics which have impacted upon the provision and process of farm schools within a specific farming community. In an attempt to understand the types of issues effecting farm schooling in this area, the attitudes of farmers, farm workers, farm- children and farm school teachers towards education are investigated. Four main issues were identified and are discussed in depth, viz: I) factors effecting the provision of black farm schools; 2) the relationship between education and the economic structure of the area; 3) the value of education; and 4) socio-economic factors effecting education in the area.
Keywords: Rural schools -- South Africa -- Northeastern Cape Province -- Ugie District; Education, Rural -- South Africa -- Ugie District; Black people -- Education -- South Africa Case studies; Education, Rural -- South Africa -- Case studies